World Interrupted: An Autoethnographic Exploration into the Rupture of Self and Family Narratives Following the Onset of Chronic Illness and the Death of a Mother - Pearce, Caroline (Qualitative Sociology Review, 2008)
Informed by the developments in autoethnography, narrative analysis and biographical sociology this paper seeks to affirm that understanding our narrative enables self-understanding and more importantly enables the understanding of others. Using an autoethnographic approach this paper explores the rupture in self and family identity following two traumatic events: the onset of a chronic illness (Multiple Sclerosis) and the death of a mother. It is the story of the life of my mother, who suffered with MS for 9 years and the story of my sister and myself, who cared for her throughout our childhood up to her death in 2000. The rupture in identity that we suffered interrupted the world in which we lived and exposed the contents of our individual and collective world(s). The themes that emerged from the narratives in this study suggest rupture is experienced as a movement of transgression that leads to movements of regression and progression.